2016
DOI: 10.1089/jmf.2015.3634
|View full text |Cite
|
Sign up to set email alerts
|

Lactoferrin Increases Antioxidant Activities and Ameliorates Hepatic Fibrosis in Lupus-Prone Mice Fed with a High-Cholesterol Diet

Abstract: Lactoferrin (LF) has beneficial effects against various diseases. However, the effects of LF on liver fibrosis in systematic lupus erythematosus (SLE) are unknown. In this study, NZB/W F1 mice were utilized to investigate the effects of LF on SLE. Experiments reveal that LF significantly increases glutathione and 1,1-diphenyl-2-picryl-hydrazyl levels and significantly decreased malondialdehyde levels in both serum and liver in NZB/W F1 mice. LF also lowered matrix metalloproteinase-9 activity and liver inflamm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 33 publications
2
6
0
Order By: Relevance
“…Among the secreted proteins upregulated in the FGF21_ADSCs CM, we noted that α‐LA and LTF might be involved in the inhibition of fibrogenic activity. α‐LA and LTF have a liver protective and anti‐fibrotic effect, respectively . We confirmed that α‐LA or LTF treatment inhibited TGF‐β‐induced α‐SMA and Col1a1 expression in LX‐2 cells.…”
Section: Discussionsupporting
confidence: 71%
See 3 more Smart Citations
“…Among the secreted proteins upregulated in the FGF21_ADSCs CM, we noted that α‐LA and LTF might be involved in the inhibition of fibrogenic activity. α‐LA and LTF have a liver protective and anti‐fibrotic effect, respectively . We confirmed that α‐LA or LTF treatment inhibited TGF‐β‐induced α‐SMA and Col1a1 expression in LX‐2 cells.…”
Section: Discussionsupporting
confidence: 71%
“…α-LA and LTF have a liver protective and anti-fibrotic effect, respectively. 10,11 We confirmed that α-LA or LTF treatment inhibited TGF-β-induced α-SMA and Col1a1 expression in LX-2 cells.…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…With regard to the liver, decreased IL-1β by LF leads to the inhibition of carbon tetrachloride-induced hepatitis in a rat model [ 18 ]. Another report suggests that LF reduced the expression of TGF-β1, IL-1β, and TNF-α and suppressed liver fibrosis in a rat systemic lupus erythematosus model [ 19 ]. The anti-tumor abilities of LF have also been described in various cancer cell lines, such as those of the breast [ 20 ], stomach [ 21 ], head, and neck [ 22 ].…”
Section: Introductionmentioning
confidence: 99%